PERSEPSI PETANI SAYURAN KUBIS, PETSAI DAN WORTEL TERHADAP PESTISIDA ORGANIK DI KELURAHAN KAKASKASEN III KECAMATAN TOMOHON UTARA KOTA TOMOHON - Yemi ., Nagapa; Grace Adonia Josefina Rumagit; Caroline Besty Diana Pakasi (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the perceptions of farmers of cabbage, Chinese cabbage and carrots on the use of organic pesticides in the Village of Kakaskasen III, North Tomohon Sub-district, Tomohon City. The study lasts for three months starting from November 2018 to January 2019. The method used in this study is the survey method. Selection of respondents was purposevely. This study used primary data and secondary data. Primary data was collected by interviewing directly with 39 farmers based on a questionnaire that had been prepared previously. Secondary data was obtained from the Village Office of Kakaskasen III, Tomohon Utara Sub-district, local bookstore, and internet through google scholar to get electronic books, journalarticles and theses related to the topic of research on vegetable farmers' perceptions of organic pesticides. The data analysis used in this study was descriptive analysis method and used likert scale analysis. The results showed that the total score of perceptions of farmers of cabbage, cabbage and carrot vegetables on organic pesticides in the Village of Kakaskasen III, amounted to 1,153, were in the category of hesitant perceptions with a percentage value of 59.1% so included in the poor category.